Two new species of Macrodactylus (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) from Mexico and Guatemala - Arce-Pérez, Roberto; Reynoso-Velasco, Daniel (Zootaxa, 2021)
Two new species of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) from Mexico and Guatemala are described and illustrated: Macrodactylus miguelangeli new species from Mexico and Guatemala, and M. oaxacaensis new species from Mexico. With the descriptions of these two new species, the total number of species of the genus reaches 124. The characteristics of two closely related species are briefly discussed.